A subanalysis of Taiwanese patients from ODYSSEY South Korea and Taiwan study evaluating the efficacy and safety of alirocumab. Issue 4 (April 2019) - Chao, Ting-Hsing; Hsiao, Pi-Jung; Liu, Ming-En; Wu, Chiung-Jen; Chiang, Fu-Tien; Chen, Zhih-Cherng; Chen, Ching-Pei; Yeh, Hung-I; Lee, Tsong-Hai; Chiang, Chern-En
Abstract : Background: Alirocumab can provide significant reductions in low-density lipoprotein cholesterol (LDL-C). However, data regarding its efficacy and safety in Asians are limited. Methods: A subgroup analysis of Taiwanese patients (n = 116) in a randomized trial evaluating the efficacy and safety of alirocumab in South Korea and Taiwan (ODYSSEY KT, clinicaltrials.gov Identifier: NCT02289963) was performed. Patients with hypercholesterolemia at high cardiovascular risk on maximally tolerated statin were randomized to alirocumab (75 mg every 2 weeks; with dose increased to 150 mg at Week 12 if LDL-C ≥ 70 mg/dL at Week 8) or placebo for 24 weeks. The primary efficacy endpoint was the percent change in LDL-C from baseline to Week 24. Safety was assessed for a total of 32 weeks. Results: At Week 24, the percent change in calculated LDL-C in the alirocumab group (n = 57) was −51%, whereas that in the placebo group (n = 59) was 2.5%. Alirocumab significantly improved other lipid parameters, including non-high-density lipoprotein cholesterol, apolipoprotein B and A1, lipoprotein (a), high-density lipoprotein cholesterol, and total cholesterol. A significantly higher proportion of patients in the alirocumab group reached an LDL-C target below 70 mg/dL than those in the placebo group (81.3% vs 15.4%). The incidence of treatment-emergent adverse events was comparable between both groups. Conclusion: Alirocumab treatment provided a favorable effect on LDL-C levels and other lipid parameters, and was generally well-tolerated in patients from Taiwan. The results of current analysis were consistent with the overall ODYSSEY phase 3 program.